Abordajes periodísticos realizados por el Telégrafo y el Universo de la campaña la mano negra de chevron, periodo 2013-2017 - Rita Elizabeth, Villarroel Ponce (2020)
The aim of this research was to identify the journalistic approaches carried out by El Telégrafo and El Universo at the campaign “La Mano Negra de Chevron” from 2013 to 2017. This research studied the end of this campaign and how it contributed to the Chevron case. A qualitative and descriptive research is employed since the content and ways of presenting the information in its printed version were analyzed. It was necessary to employ the Communicational theory of Functionalism as it studies the messages broadcast through the mass media. Researchers worked with scientific, historical, logical, inductive and analytical methods. This research is based on what is said and how it says from publications made on the subject such as approaches, journalistic genres and location. For data collection purposes, content analysis matrices designed for this project are used in addition to other criteria interpretation tools such as interviews with print experts. Two-hundred-sixty-four publications of the two media were analyzed and studied. It was obtained as a result of the analysis of these media that the journalistic genre most used was the informative note. This is why, the research essentially looked at approaches and ways of dealing with information. Finally, it is proposed to produce a multimedia product with the handling of the information of the campaign “The Black Hand of Chevron” in order to make known the informative treatment of these media on the case.